Comparative genomics of three non-hematophagous leeches (Whitmania spp.) with emphasis on antithrombotic biomolecules - Zhao, Fang; Huang, Zuhao; Tang, Lizhou; Zhang, Wenting; Liu, Zichao; Lin, Gonghua (Frontiers in Genetics, 2025)
Leeches are well known for blood-feeding habits and are widely used for medicinal purposes as they secrete various antithrombotic substances. However, some leeches exhibit non-hematophagous habits and their significance for medicinal use is controversial. Here we provide the chromosome-level genomes of two non-hematophagous leeches, Whitmania acranulata and Whitmania laevis, and, in combination with previous results from Whitmania pigra, we compared these genomes with an emphasis on antithrombotic biomolecules. All three species had the same chromosome number of 11. The genome size, repeat site percentage, and number of protein-coding genes of W. laevis (173.87 Mb, 28.28%, 23,818) were similar to those of W. pigra (169.37 Mb, 27.02%, 24,156), whereas these values of W. acranulata (181.72 Mb, 29.55%, 27,069) were higher than those of the other two leeches. W. laevis was a monophyletic clade of W. pigra, whereas W. acranulata had a paraphyletic relationship with W. pigra. The number of antithrombotic genes in W. laevis (N = 76) was similar to that of W. pigra (N = 79), whereas W. acranulata (N = 102) had apparently more such genes. Of the 21 gene families, 9 and 11 were differentially expressed in W. acranulata and W. laevis compared to W. pigra, respectively. The expression profiles of the antithrombotic gene families were more similar between W. acranulata and W. laevis. Although there were several cases of gene loss or pseudogenization, most antithrombotic genes of the three Whitmania species were intact and transcribable. These results provide valuable insights into the evolution of non-hematophagous leeches and development of antithrombotic drugs.